Scaling Up Departmental Health Insurance Units in Senegal: A Mixed-Method Study - Valéry Ridde; Mouhamadou Faly Ba; Babacar Kane; Anouk Chouaïd; Adama Faye (Taylor & Francis Group, 2024)
In response to the failure of community-based health insurance (CBHI) at the municipal level, some African countries are implementing district or departmental CBHIs to improve universal health coverage. After creating two CBHIs at the departmental level in 2014, Senegal launched a campaign to disseminate the model in 2022. This article presents the stakeholders' perspectives on the factors and challenges of scaling up CBHI departmentalization in Senegal. The study uses a mixed-methods approach, utilizing concept mapping and a focus group to examine scaling up departmentalization. The sample size consists of 22 individuals involved in the process. The quantitative analysis includes hierarchical cluster analysis, multidimensional scaling analysis, and the Pearson coefficient test. The qualitative analysis involves content analysis to triangulate the findings. Participants identified 125 factors to consider for the departmentalization of CBHI. They were categorized into nine clusters according to their degree of importance (I) and ease to organize (F): service package (I: 4.07; F: 2,26), communication (I: 4.05; F: 2.96), governance (I: 3.96; F: 2,94), human and logistical resources (I: 3.94; F: 2,82), financing (I: 3.90; F: 2,31), involvement of the authorities (I: 3.82; F: 2.75), community involvement (I: 3.81; F: 2.76), membership (I: 3.70; F: 2.24, strategic planning and implementation (I: 3.57; F: 2,62). The main challenges faced were a process perceived as precipitous and vertical and needing more negotiation and consultation. The conditions for accompaniment and public funding availability need to be sufficiently considered. The study proposes avenues for action to promote the scaling up of CBHI departmentalization in Senegal.